Multi-faceted PMN and epithelial responses triggered by S. pneumoniae PLY promote bacterial translocation across the pulmonary barrier - Xu, Shuying. (Tufts University. Tisch Library., 2024)
Thesis (Ph.D.)--Tufts University, 2024-08.; Submitted to the Dept. of Immunology.; Advisor: John Leong.; Committee: Joan Mecsas, Henry Wortis, Shumin Tan, Pilar Alcaide, Alexander Poltrack, Michael Mansour, and Marta Rodriguez-Garcia.; Keywords: Immunology, and Microbiology.